11.3k views
4 votes
In the picture down below

In the picture down below-example-1
User Roddick
by
5.3k points

1 Answer

1 vote

Answer:

Option C. f¯¹(x) = x + 3

Explanation:

f(x) = x – 3

To find the inverse, f¯¹(x) of f(x), we simply do the following:

f(x) = x – 3

Replace f(x) with y

y = x – 3

Interchange y and x

x = y – 3

Make y the subject by rearranging

x + 3 = y

y = x + 3

Replace y with f¯¹(x)

f¯¹(x) = x + 3

Therefore, the inverse of f(x) = x – 3 is f¯¹(x) = x + 3

User Terryn
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.